Post Hoc Analysis of the Impact of Lemborexant on Patient-Reported Sleep and Insomnia Severity in Adults with Insomnia and Depression Histories. (April 2022) - Culpepper, Larry; Krystal, Andrew D.; Pinner, Kate; Moline, Margaret
Abstract: Introduction: The dual orexin receptor antagonist lemborexant (LEM) is approved in multiple countries including the United States, Japan, Canada, and Australia for insomnia treatment in adults. In phase 3 study E2006-G000-303 (Study 303; SUNRISE-2; NCT02952820), LEM provided significant benefit vs placebo (PBO) on subjective sleep outcomes over 6 months and was well tolerated. This post hoc analysis evaluated the effect of LEM on sleep outcome measures and insomnia severity as assessed by the Insomnia Severity Index (ISI) over 6 months in subjects with a lifetime history of depression (DepHx subgroup). We performed this analysis as insomnia in DepHx subjects could be a residual symptom of unresolved depression, and therefore, these subjects may respond differently to insomnia treatment. Methods: Study 303 was a randomized, double-blind, 12 months global study in adults (≥18 years) with DSM-5 insomnia disorder. For 6 months (Treatment Period 1), subjects were randomized to PBO or LEM (5 mg [LEM5]; 10 mg [LEM10]). For the next 6 months (Treatment Period 2; not reported), PBO subjects were rerandomized to LEM and LEM subjects continued their original dose. The inclusion criteria allowed for participation of subjects with a lifetime DepHx, concomitant antidepressant medication use and/or mild depression (maximum Beck Depression Inventory II score of 19). Subjects had a baseline ISI total score (ISI-ts) ≥15. Results: The Full Analysis Set comprised 949 subjects, including 112 subjects in the DepHx subgroup (PBO, n = 34; LEM5, n = 39; LEM10, n = 39). Baseline median subjective sleep onset latency (sSOL; minutes) was 52.9, 57.1, and 70.7 for PBO, LEM5, and LEM10, respectively. At 6 months, greater median decreases from baseline in sSOL were observed with LEM5 (−21.7) and LEM10 (−40.1) vs PBO (−12.9). Baseline mean subjective sleep efficiency (sSE; %) was 62.2, 59.2, and 62.4 for PBO, LEM5, and LEM10, respectively. At 6 months, greater mean (SD) increases from baseline in sSE were observed with LEM5 (17.2 [18.3]) and LEM10 (20.9 [19.0]) vs PBO (14.9 [15.4]). Baseline mean subjective wake after sleep onset (sWASO; minutes) was 123.7, 151.0, and 132.6 for PBO, LEM5, and LEM10, respectively. At 6 months, greater mean (SD) decreases from baseline in sWASO were observed with LEM5 (−52.7 [69.2]) and LEM10 (−68.8 [81.9]) vs PBO (−46.7 [69.4]). Mean baseline ISI-ts were 18.6, 19.9, and 19.0 PBO, LEM5, and LEM10, respectively. At 6 months, greater mean (SD) decreases from baseline in ISI-ts were observed with LEM5 (−9.1 [6.8]) and LEM10 (−10.0 [5.9]) vs PBO (−7.9 [5.6]). Treatment-emergent adverse event rates in the DepHx subgroup were similar to those in the overall study population. Discussion: At 6 months, LEM improved patient-reported sleep outcomes and reduced patient-reported insomnia severity in subjects with DepHx. These results suggest that LEM may be a therapeutic option for patients with insomnia and DepHx. Funding: Eisai, Inc.